'There were some clues': a qualitative study of heuristics used by parents of adolescents to make credibility judgements of online health news articles citing research. Issue 8 (26th August 2020) - Maggio, Lauren A; Krakow, Melinda; Moorhead, Laura L
Abstract : Objective: To identify how parents judge the credibility of online health news stories with links to scientific research. Design: This qualitative study interviewed parents who read online stories about e-cigarettes and human papillomavirus (HPV) vaccination published by top-tier US news organisations. Researchers asked participants to describe elements of a story that influenced their judgement about content credibility. Researchers analysed transcripts using inductive and deductive techniques. Deductive analysis drew on cognitive heuristics previously identified as being used by the public to judge online health information. Inductive analysis allowed the emergence of new heuristics, especially relating to health. Setting: The US National Cancer Institute's Audience Research Lab in Maryland, in August–November 2018. Participants: Sixty-four parents with at least one child between the ages of 9 and 17 residing in Maryland, Virginia, or the District of Columbia participated. Researchers randomly assigned 31 parents to the HPV vaccination story and 33 to the e-cigarette story. Results: Evidence of existing heuristics, including reputation, endorsement, consistency, self-confirmation, expectancy violation and persuasive intent emerged from the interviews, with participants deeming stories credible when mentioning physicians (reputation heuristic) and/or consistent with information provided by personal physicians (consistency heuristic). Participants also described making credibility judgements based on presence of statistics, links to scientific research and their general feelings about news media. In relation to presence of statistics and links, participants reported these elements increased the credibility of the news story, whereas their feelings about the news media decreased their credibility judgement. Conclusions: Parents used a constellation of heuristics to judge the credibility of online health news stories. Previously identified heuristics for online health information are also applicable in the context of health news stories. The findings have implications for initiatives in education, health communication and journalism directed towards increasing the public's engagement with health news and their credibility judgements.